1999
DOI: 10.3171/jns.1999.90.3.0448
|View full text |Cite
|
Sign up to set email alerts
|

Failure of third ventriculostomy in the treatment of aqueductal stenosis in children

Abstract: Third ventriculostomy effectively controls obstructive triventricular hydrocephalus in more than 70% of children and should be preferred to placement of extracranial cerebrospinal shunts in this group of patients. When performed using ventriculographic guidance, the technique has a higher mortality rate and a higher failure rate in children younger than 6 months of age and is, therefore, no longer preferred. When third ventriculostomy is performed using endoscopic guidance, the same long-term results are achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
170
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(182 citation statements)
references
References 15 publications
8
170
0
4
Order By: Relevance
“…However, a longer follow-up period is undoubtedly required, since delayed failure following ETV has been reported even 5.9 years following the procedure [20]. In our series ETV failed after 2 years in a patient with postmeningitic hydrocephalus despite an excellent initial result.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, a longer follow-up period is undoubtedly required, since delayed failure following ETV has been reported even 5.9 years following the procedure [20]. In our series ETV failed after 2 years in a patient with postmeningitic hydrocephalus despite an excellent initial result.…”
Section: Discussionmentioning
confidence: 75%
“…However, Grant and McLone [1]and Buxton et al [5]reported success rates as high as 23% in an unselected group of children less than 1 year old and recommended that ETV should be used as first-line treatment for hydrocephalus in this age group to avoid shunt-related morbidity, mortality, and economic implications. In a retrospective study of 213 children with obstructive hydrocephalus, Cinalli et al [20]reported that when third ventriculostomy was performed with endoscopic guidance, no difference was found in the long-term outcome between children younger than 6 months and older ones. The authors suggested that this improved long-term outcome could be due to more accurate patient selection and/or the technical advantages of endoscopy as compared with ventriculographic guidance, allowing direct visualization of the third ventricular floor and the anatomical landmarks of the interpeduncular cistern.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, young children with open sutures are not able to generate a sufficient pressure gradient across the arachnoid granulations for reabsorption [25]. Some authors report substantially better results with success rates between 57 and 87% [26, 27]. For these authors, the reported poor results are not related to the immaturity of the CSF pathways but to poor selection criteria for ETV.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, if TV fails in the future, the shunt can be unligated if we leave the shunt system in place. In order to justify VP shunt removal, we also have to consider the long-term outcome of TV [15, 20]compared with VP shunt. At the time of writing, such reports are still few in number.…”
Section: Discussionmentioning
confidence: 99%